2022
DOI: 10.1155/2022/4628539
|View full text |Cite
|
Sign up to set email alerts
|

Development of Robust Guaranteed Cost Mixed Control System for Active Suspension of In-Wheel-Drive Electric Vehicles

Abstract: This paper presents a mixed H2/H∞-based robust guaranteed cost control system design of an active suspension system for in-wheel-independent-drive electric vehicles considering suspension performance requirements and parameter variation. In the active suspension system model, parameter uncertainties of active suspension are described by the bounded method, and the perturbation bounds can be also limited; then, the uncertain quarter-vehicle active suspension model where in-wheel motor is suspended as a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Jin et al 6466 used the Active Suspension of In-Wheel-Drive Electric Vehicles (IWMD-EV) solution. In order to achieve better driving comfort and reduce the force applied to the motor bearing in the wheel, a robust H dynamic output feedback controller 64,66 and μ -Synthesis Methodology 65 have been derived so that the closed loop system has asymptotic stability and simultaneously satisfies stress performance such as road holding, suspension travel, dynamic load applied to bearings, and limitation of actuators. Finally, the simulation results demonstrated that the proposed controller offered better suspension performance despite the faults of the actuators and the time delay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jin et al 6466 used the Active Suspension of In-Wheel-Drive Electric Vehicles (IWMD-EV) solution. In order to achieve better driving comfort and reduce the force applied to the motor bearing in the wheel, a robust H dynamic output feedback controller 64,66 and μ -Synthesis Methodology 65 have been derived so that the closed loop system has asymptotic stability and simultaneously satisfies stress performance such as road holding, suspension travel, dynamic load applied to bearings, and limitation of actuators. Finally, the simulation results demonstrated that the proposed controller offered better suspension performance despite the faults of the actuators and the time delay.…”
Section: Resultsmentioning
confidence: 99%
“…Jin et al [64][65][66] used the Active Suspension of In-Wheel-Drive Electric Vehicles (IWMD-EV) solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This algorithm is established based on the theory of H 2 and H ∞ with oscillating state matrices [ 17 ]. Today, the Robust control algorithm can be applied to the suspension system model of passenger cars, heavy trucks, and electric vehicles [ 18 , 19 ]. For systems oscillating continuously under different conditions, an Adaptive control algorithm is a suitable choice [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, active suspension is gradually being widely used, and many papers have proposed control methods of active suspension, such as H-infinity control [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%